2007
DOI: 10.1303/aez.2007.189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod and temperature on preimaginal development and summer diapause of Chrysocharis pubicornis (Zetterstedt) (Hymenoptera: Eulophidae), a pupal parasitoid of leafminers (Diptera: Agromyzidae)

Abstract: The preimaginal development of Chrysocharis pubicornis was studied at different temperatures and 14L:10D photoperiod. The lower developmental threshold was 7.4 and 7.2°C, and the thermal constant was 297.4 and 307.5 degree-days for males and females, respectively. The effects of combinations of different temperatures and photoperiods on larval diapause induction and termination were also examined. Larval development showed a short-day type response affected by temperature. The percentage of individuals enterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…The post-diapause development time of H. armigera pupae was 2-3 days after termination of the high-temperature treatment (Liu et al, 2006). Other insects that exhibit summer diapause have similar responses, including Adelges japonicus Monzen (Tabuchi et al, 2009), Nicrophorus quadripunctatus Kraatz (Nishimura, 2010) and Chrysocharis pubicornis Zetterstedt (Larios, 2007). B. odoriphaga 4th instar larvae clearly possess the potential capacity to survive the hot summer months in a diapause-like state, which is similar to that of Adelges japonicus Monzen (Tabuchi et al, 2009) (Gou et al, 2020;Zhu et al, 2021).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The post-diapause development time of H. armigera pupae was 2-3 days after termination of the high-temperature treatment (Liu et al, 2006). Other insects that exhibit summer diapause have similar responses, including Adelges japonicus Monzen (Tabuchi et al, 2009), Nicrophorus quadripunctatus Kraatz (Nishimura, 2010) and Chrysocharis pubicornis Zetterstedt (Larios, 2007). B. odoriphaga 4th instar larvae clearly possess the potential capacity to survive the hot summer months in a diapause-like state, which is similar to that of Adelges japonicus Monzen (Tabuchi et al, 2009) (Gou et al, 2020;Zhu et al, 2021).…”
Section: Discussionmentioning
confidence: 65%
“…Some insects survive high summer temperatures in a summer diapause, estivation, heat dormancy or development delay (Denlinger et al, 2002(Denlinger et al, & 2014. These species include Heliothis assulta (Liu et al, 2006), Adelges japonicus (Tabuchi et al, 2009), Colaphellus bowringi (Kuang et al, 2011) and Chrysocharis pubicornis (Larios et al, 2007). Regardless of the insect adaptations used to survive adverse environmental conditions, complex biological and physiological responses are involved (Neven, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that 10 h light '12 8C could be a better condition for aestivation termination. Larios et al (2007) also report that in a pupal parasitoid of leafminers, Chrysocharis pubicornis (Zetterstedt), shorter day-length and lower temperature can increase aestivation termination rate.…”
Section: Discussionmentioning
confidence: 93%
“…Various studies suggest that the day-length and temperature are the major factors causing diapause in parasitoids (Tauber et al 1986;Milonas & Savopoulou-Soultani 2000;Jervis et al 2005;Larios et al 2007) although other factors, such as host and host-plant effects may also play a role (Tauber et al 1986;Boivin 1994;Polga´r & Hardie 2000). The ability to induce and terminate diapause in the laboratory has important implications for the use of parasitoids in biological control programmes (Laing & Corrigan 1995;Milonas & SavopoulouSoultani 2000;Mehrnejad and Copland 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Por exemplo, Honda & Kainoh (1998) mostraram que fêmeas mais velhas do parasitóide Ascogaster reticulatus Watanabe, são capazes de depositar maior número de ovos bem como associar odores de plantas ao hospedeiro. Além disso, fatores como fotoperíodo, temperatura e disponibilidade de hospedeiros podem afetar tanto o comportamento de parasitóides, interferindo na sua atividade e capacidade de busca pelo hospedeiro, como o seu ciclo biológico, afetando sua longevidade, fecundidade e diapausa (Bai & Smith 1993, Sagarra et al 2000, Tatsumi & Takada 2005, Larios et al 2007.…”
unclassified